PENERAPAN PENDEKATAN BEHAVIORAL OPERANT CONDITIONING PADA PEMBELAJARAN PAI DI SMA NEGERI 3 GOWA - Rahayu, Agustina; Ismail, Wahyuni; ., Saprin (Inspiratif Pendidikan, 2018)
This study aims to find out the application of behavioral operant conditioning approach in learning Islamic education in state high school 3 Gowa, knowing the supporting factors and inhibiting the application of behavioral operant conditioning approach in Islamic education learning in state high school 3 Gowa and to know the result of applying behavioral operant conditioning approach on Islamic education learning in state high school 3 Gowa. The type of research used is descriptive qualitative research. This thesis uses primary and secondary data sources. Methods of data collection are observation, interview and documentation. Data analysis is data reduction, display data (presentation of data) and conclusion. The results showed that the implementation of behavioral operant conditioning approach on learning Islamic education in state high school 3 Gowa has been running well because Islamic education teachers have made lesson plans, implement learning according to lesson plan and evaluate to students on each sub-subject matter that can not be separated from provision of positive and negative reinforcement, although sometimes in the implementation of learning is less in accordance with the lesson plan that has been made by teachers Islamic education. In addition, after applying the behavioral operant conditioning approach to Islamic education learning in state high school 3 Gowa teachers also gained advantages and disadvantages of behavioral operant conditioning approach. The advantages obtained are students more enthusiastic and competing in following the learning process, can change student behavior to be better and motivated students in order to learn more enterprising. While the lack of a student who feels envy to students who excel and student behavior more wins.